A review of Grammarly studies in the EFL context in Indonesia - Zainurrahman Zainurrahman; Rojab Siti Rodliyah; Emi Emilia (Universitas Islam Sultan Agung, 2026)
Grammarly has been a popular automated writing evaluation (AWE) tool incorporated in English as a Foreign Language (EFL) writing instruction. Grammarly studies have also proliferated. However, the trends of Grammarly studies in this context have not been captured sufficiently. To fill this gap, this study reviews the trends of Grammarly studies in Indonesia, classifying published studies from 2014 to 2024 (the search occurred in March 2024). To this end, Grammarly studies were retrieved from the Sinta database and Google Scholar via Publish or Perish 8. The inclusion criteria determined that 11 studies were to be included. Using content analysis, research types, topics, instruments, methods, and key findings are classified and reported. The analysis showed that qualitative research was the most widely used method, followed by quantitative research. Meanwhile, research and development (R&D) and classroom action research (CAR) are extremely scant. Additionally, most studies have focused more on students’ perception of Grammarly than its actual performance. These findings suggest that further CAR-based, experimental, and correlational studies on the use of Grammarly in Indonesia are needed to address the research gaps identified. The study provides useful insights that can serve as a basis for future research on the use of Grammarly in language teaching and applied linguistics, especially in Indonesia.